2009
DOI: 10.1128/jb.01726-08
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Alarmone (p)ppGpp Mediates Stress Responses, Vancomycin Tolerance, and Virulence inEnterococcus faecalis

Abstract: The stringent response is a global bacterial response to stress that is mediated by accumulation of the alarmone (p)ppGpp. In this study, treatment with mupirocin was shown to induce high levels of (p)ppGpp production in Enterococcus faecalis, indicating that this nosocomial pathogen can mount a classic stringent response. In addition, (p)ppGpp was found to accumulate in cells subjected to heat shock, alkaline shock, and inhibitory concentrations of vancomycin. Sequence analysis of the E. faecalis genome indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
245
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(264 citation statements)
references
References 56 publications
15
245
0
4
Order By: Relevance
“…Specifically, the (p)ppGpp 0 strain displays increased sensitivity to macrophages, impaired growth and survival in serum or whole blood, and attenuated virulence in animal models (6)(7)(8). In this report, we show that these phenotypes are intimately associated with metal homeostasis.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Specifically, the (p)ppGpp 0 strain displays increased sensitivity to macrophages, impaired growth and survival in serum or whole blood, and attenuated virulence in animal models (6)(7)(8). In this report, we show that these phenotypes are intimately associated with metal homeostasis.…”
Section: Discussionmentioning
confidence: 71%
“…3B). Even though the Δrel Ef strain displays intrinsically higher (p)ppGpp levels due to the absence of (p)ppGpp hydrolase activity (6,18), the lack of pppGpp accumulation in this strain indicated that Rel Ef is responsible for (p)ppGpp accumulation in response to metal starvation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations